irulence analysis and influence of soil pattern and agronomic practices with respect to Ganoderma foot rot of arecanut in southern Karnataka - S. Basavaraj, K.R. Shreenivasa, K.B. Palanna*, T. Narendrappa (Journal of Plantation Crops, 2018)
The foot rot of arecanut, caused by Ganoderma, is one of the most important constraint limiting arecanut production and productivity in South Karnataka. The incidence of foot rot of arecanut during the year 2014-15 ranged from 0 to 55 per cent in southern dry tracts of Karnataka. Among the four districts surveyed, Tumkur recorded the maximum disease incidence (19.3%) followed by Chitradurga (18.1%) and Hassan (4.3%). Ganoderma sporophore and infected root bits of arecanut were found ideal source for isolation, as they yielded 52.9 and 46.4 per cent of the isolates, respectively. Foot rot was noticed in mono crop as well as mixed crop of arecanut and coconut. Among the 15 taluks surveyed, Chikanayakanahally had the maximum incidence (34.0%) followed by Gubbi and Holalkere which accounted 28.8 and 27.2 per cent, respectively. The minimum per cent incidence (1.8%) was observed in Beluru taluk of Hassan district. Among the different soil types, maximum incidence (13.5%) was observed in sandy soils followed by red soils (8.9%). Canal irrigated gardens accounted maximum the incidence (12.7%) compared with bore-well irrigated gardens and those under rainfed conditions. Similarly, gardens under flood irrigation recorded 15.1 per cent of maximum incidence compared to gardens under drip, basin/sprinkler irrigation systems and gardens under regular cultivation recorded the maximum incidence compared to uncultivated gardens. Virulence of 10 Ganoderma isolates of arecanut tested under pot culture revealed that isolate AG 9, recorded maximum disease severity index (75 DSI) nine months after inoculation followed by AG 22 and AG 4 which accounted 68.8 DSI each.